Moralizing the West: Multimodal Constructions of Civilizational Decline in Pro-Russian Arabic-Language Discourse on X - Pryimak, Oleksii (Український політико-правовий дискурс, 2026)
Purpose. The purpose of the article is to examine how the West is discursively and multimodally constructed in pro-Russian Arabic-language accounts on X. The article focuses on the ways in which anti-Western meanings are produced through the interaction of textual, visual, and symbolic resources. Special attention is paid to how individual episodes, images, videos, and evaluative captions are transformed into broader moral and civilizational generalizations about Western societies. Methods. The study applies multimodal critical discourse analysis as the main methodological framework. This approach makes it possible to analyze the interaction between verbal messages, images, videos, symbolic markers, and platform-specific forms of communication. The empirical material consists of publications by selected Arabic-language accounts on X that systematically disseminate pro-Russian and anti-Western narratives. The analysis focuses on recurring evaluative patterns, visual framing, symbolic oppositions, discursive scaling, and the role of captions in assigning moral and political meaning to visual materials. Results. The analysis shows that the West is systematically represented as a symbolic space of moral disorder, cultural decline, erosion of traditional norms, and destabilizing influence on other societies. This representation is produced through repeated references to gender, sexuality, family norms, public behavior, cultural practices, and cooperation with Western political institutions. Visual materials are used as seemingly direct evidence, while accompanying captions provide the preferred interpretive frame. Individual visual episodes are generalized and presented as signs of wider moral and civilizational processes. The study also finds that anti-Western representation performs a function of discursive self-positioning: by negatively evaluating the West, the analyzed accounts implicitly construct their own position as bearers of an alternative normative standpoint connected with their broader pro-Russian orientation. Conclusions. The article concludes that anti-Western discourse in the analyzed publications operates through a stable multimodal mechanism: visual fragments provide apparent immediacy, captions assign evaluative meaning, and repeated interpretive patterns transform isolated episodes into broader claims about Western societies and Western influence. The West is represented not only through political criticism, but through a moral and civilizational register in which cultural practices, family norms, and public behavior become markers of decline. The findings deepen the understanding of digital political communication in the Arabic-language segment of X and of the mechanisms through which pro-Russian narratives adapt to non-Western information environments.